Radiation Dose from Adult and Pediatric Multidetector Computed Tomography - Tack, D.; Gevenois, Pierre Alain; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
The number of computed tomography (CT) examinations has increased continuously since 1980 for a variety of reasons, including new indications and growth in the number of CT units. Beyond its use in adults with suspected malignancies and other conditions, CT is now used in young patients, including children, who are suffering from benign diseases and have a long life expectancy. The consequence of this trend is that CT, and in particular multidetector row CT (MDCT), is now responsible for about two-thirds of the total radiation dose delivered to the population for diagnostic purposes. Because of the associated radiation dose, CT may induce cancers, and the risk of death has been estimated at up to one per 1,000 CT examinations. Even if the balance between the risks related to ionizing radiation and the benefits from an accurate diagnosis provided by CT scanning has always been considered highly positive, it is now mandatory to reduce and/or to optimize the radiation dose. Referring clinicians, radiologists, and technologists should therefore all understand the mechanisms that determine the radiation risk, but it has been shown that only a small proportion of these professionals are aware of both the radiation risks and their underlying mechanisms. This book is designed to rectify this situation. The first part of the book provides a comprehensive approach to all the factors that influence the radiation dose and subsequently the risk induced by using MDCT in children and adult patients. In the second part, guidelines are proposed for optimization of the radiation dose in order to obtain an image quality sufficient for appropriate diagnostic performance while restricting the dose delivered. The authors are experts of international standing, selected for their acknowledged scientific contributions. This book will appeal to both general and specialized radiologists, including pediatric radiologists, CT technologists, physicists, manufacturers, and all professionals involved in MDCT.
Clinical Expansion of CT and Radiation Dose -- Clinical Expansion of CT and Radiation Dose -- Radiation Risks in Multidetector CT -- Risks from Ionising Radiation -- The Cancer Risk from Low-Level Radiation -- CT Parameters that Influence the Radiation Dose -- Collective Radiation Dose from MDCT: Critical Review of Surveys Studies -- Methods and Strategies for Radiation Dose Optimization — and Reduction — in MDCT with Special Focus on the Image Quality -- Automatic Exposure Control in Multidetector-Row Computed Tomography -- Patient Centering in MDCT: Dose Effects -- Clinical Approaches of Dose Optimization and Reduction -- Dose Optimization and Reduction in CT of the Head and Neck, Including Brain -- Dose Reduction and Optimization in Computed Tomography of the Chest -- Dose Optimization and Reduction in MDCT of the Abdomen -- Optimization of Radiation Dose in Cardiac and Vascular Multirow-Detector CT -- Dose Optimization and Reduction in CT of the Musculoskeletal System Including the Spine -- Dose Reduction in CT Fluoroscopy -- Dose Optimization and Reduction in CT of Children -- Radiation Risk Management in Low Dose MDCT Screening Programs -- Radiation Risk Management in Low Dose MDCT Screening Programs.
Keywords: Radiology; Pediatrics; Neuroradiology; Internal medicine; Imaging / Radiology; Diagnostic Radiology; Pediatrics; Neuroradiology; Internal Medicine